Upaya Mendorong Pembelajaran Efektif Masa Pandemi Melalui Pelatihan Inovasi Belajar Berbasis Digital - Zailani Surya Marpaung; Slamet Widodo; Nurmah Semil; Mardianto Mardianto (STMIK Royal, 2021)
Abstract: Pandemic Covid-19 has had a direct impact on the world of education. The limitation of the crowd in community activities in public places causes the world of education to maximize the use of information and communication technology as a medium for distance learning or online. This encourages educators/ teachers to formulate alternatives for distance learning media by adapting them according to the conditions of available facilities and infrastructure, and mastering the use of a number of digital platforms that can be used as alternative learning media. This digital-based learning innovation training activity aims to introduce and assist the use of several digital learning media in one of the schools, namely SMK Lingua Prima Indralaya. Assessment of the success of the training held was carried out through a pretest and post-test. Assistance is carried out so that teachers understand and gain insight in formulating innovative learning methods in the implementation of the distance or online teaching and learning process. In this training, introduction and assistance were carried out related to the use of audio podcasts, maximizing the function of social media and also designing materials with attractive and innovative PowerPoint templates.Keywords: digital based learning; effective learning; pandemic period Abstrak: Pandemi Covid-19 telah berdampak secara langsung terhadap dunia pendidikan. Dibatasinya kerumunan dalam aktivitas masyarakat ditempat umum menyebabkan dunia pendidikan harus memaksimalkan penggunaan teknologi informasi dan komunikasi sebagai media pembelajaran jarak jauh atau daring. Hal ini mendorong tenaga pendidik / guru harus merumuskan alternatif-alternatif media pembelajaran jarak jauh dengan cara mengadaptasinya sesuai dengan kondisi sarana dan prasarana yang tersedia, serta menguasai penggunaan sejumlah platform digital yang dapat digunakan sebagai media pembelajaran alternatif. Kegiatan pelatihan inovasi belajar berbasis digital ini bertujuan untuk melakukan pengenalan dan pendampingan penggunaan beberapa media pembelajaran digital di salah satu sekolah, yakni SMK Lingua Prima Indralaya. Penilaian terhadap keberhasilan pelatihan yang diselenggarakan ini dilakukan melalui pretest dan post-test. Pendampingan dilakukan agar para guru memahami dan menambah wawasan dalam merumuskan metode pembelajaran yang inovatif dalam pelaksanaan proses belajar mengajar jarak jauh atau daring. Pada pelatihan ini dilakukan pengenalan dan pendampingan terkait penggunaan podcast audio, memaksimalkan fungsi media sosial dan juga merancang materi dengan template powerpoint yang menarik dan inovatif.Kata Kunci: masa pandemi; pembelajaran berbasis digital; pembelajaran efektif